Tanggung Jawab Hukum Pengelolaan Dana Bantuan Operasional Sekolah Di SD Negeri 1 Kunjeng Kecamatan Gubug Kabupaten Grobogan - Marshanda Salsadella; Edi Pranoto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Schools, as educational facilities, have a crucial role in improving the quality and standards of national education to make it more advanced. In line with the introduction to PERMENDIKBUD No. 18 of 2019, the government provides compensation in the form of School Operational Assistance Funds (BOS) with the aim of helping fund school operational and non-personnel costs. Implementing school operational assistance is part of the state's responsibility to provide financing to the entire community and is an implementation of the mandate of the 1945 Constitution of the Republic of Indonesia to make the nation's life intelligent. Therefore, the author is interested in analyzing it in research entitled